Transformasi Sosiologi Pendidikan dalam Islam Perkembangan Pemikiran dan Kontribusi Para Cendekiawan Muslim - Avrielya Maulida; Nasimatullaili Nasimatullaili; Dwi Maulida; Try Nurahmad Slamet Hariono; Mu’allimin Mu’allimin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research examines the transformation of educational sociological thinking in Islam, with a focus on the contributions of classical scholars such as Al-Ghazali, Ibn Khaldun, and Al-Farabi. These three figures integrate education with social, moral and spiritual values, creating a holistic approach that not only emphasizes intellectual development, but also character formation. Al-Ghazali emphasized the importance of balanced education between worldly and ukhrawi knowledge, while Ibn Khaldun, through al-umran theory, viewed education as a tool to maintain social cohesion and build a just civilization. Al-Farabi, with his thoughts about the ideal society, emphasized the role of education in creating virtuous individuals. The research method used is a literature review with a qualitative-descriptive approach to analyze the relevance of these thoughts in facing contemporary educational challenges. The results show that even though they come from different historical contexts, their thoughts remain relevant, especially in responding to today's educational challenges which prioritize a balance between science, morality and spirituality. Thus, the contribution of sociological thought to education in Islam has had a significant impact on the social structure and development of Muslim education to date.